Pengaruh Organization Citizenship Behaviour (OCB) Dan Lingkungan Kerja Terhadap Stres Kerja Pada PT. Sinar Murni Indopinting Dimoderasi Oleh Well-Being - Frida Aprilia Damayanti; Wahyu Eko Pujianto (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
Human resources are the engine of the company's activities and the company's most important asset. The theme developed at PT. Sinar Murni Indoprinting. an indication that employees have not worked optimally, this is an indication of performance that has not reached the target. Not all employees follow OCB behavior, pay attention to the work environment and some employees experience work stress. Health is the dream of every employee, both consciously and unconsciously. The purpose of this study was to analyze the effect of OCB on work stress, the influence of the work environment on work stress, the influence of work environment welfare, and the influence of OCB on employee welfare. The results showed that OCB has no effect on work stress, work environment has a significant effect on work stress, work environment has a significant effect on employee welfare, OCB has no effect on work stress on employee performance, and employee performance. environment shapes employee performance. Employees Do not disturb employees when work is stressful.